Pneumococcal conjugate vaccine triggers a better immune response than pneumococcal polysaccharide vaccine in patients with chronic lymphocytic leukemia A randomized study by the Swedish CLL group. Issue 25 (14th June 2018) - Svensson, Tobias; Kättström, Magdalena; Hammarlund, Ylva; Roth, Daniel; Andersson, P.-O.; Svensson, Magnus; Nilsson, Ingmar; Rombo, Lars; Cherif, Honar; Kimby, Eva
Highlights: First trial comparing a conjugated vaccine with a capsular polysaccharide vaccine against pneumococci in CLL. Improved immunological response against pneumococci with a conjugated vaccine in patients with CLL. Long disease duration and low IgG levels associated with poor response to pneumococcal vaccine in CLL. Abstract: Aim: To determine if patients with untreated chronic lymphocytic leukemia (CLL) benefit from vaccination with a 13-valent pneumococcal conjugated vaccine (PCV13), Prevenar13®, compared to a 23-valent pneumococcal polysaccharide vaccine (PPSV23), Pneumovax®, in terms of immune response. Background: Streptococcus pneumoniae causes substantial morbidity in patients with CLL, a group known to respond poorly to polysaccharide vaccines. Comparative studies with conjugated vaccines are lacking. Methods: 128 treatment naïve CLL patients from eight hematology clinics in Sweden were randomized to vaccination with PCV13 (n = 63) or PPSV23 (n = 65) after stratification by IgG level and CLL clinical stage (Rai). Blood samples for evaluation of immune response were obtained at baseline, and at one and six months after vaccination. Analyses for each of the 12 pneumococcal serotypes common for PCV13 and PPSV23 were performed by opsonophagocytic assay (OPA) and enzyme-linked immunosorbent assay (ELISA). Results: PCV13 elicited a superior immune response than PPSV23 in 10/12 serotypes one month after vaccination and in 5/12 serotypes six months after vaccination, measured as OPA geometric mean titers (GMTs). Geometric mean concentrations of serotype-specific IgG antibodies elicited by PCV13 as measured by ELISA, were higher than those elicited by PPSV23 in half of the common serotypes, both after one and six months. PPSV23 did not trigger a better immune response than PCV13 for any of the serotypes, regardless of analysis method or time point of analysis. Negative predictive factors for vaccination response were hypogammaglobulinemia and long disease duration. Both vaccines were well tolerated. Conclusions: In patients with previously untreated CLL, the efficacy of PCV13 in terms of immune response is superior to PPSV23 for most serotypes common for the two vaccines. We therefore propose that PCV13 should be included in vaccination programs against Streptococcus pneumoniae for CLL patients and administered as early as possible during the course of the disease.